Modern potential of bismuth in gastroenterology - A. A. Sheptulin; M. A. Vise-Khripunova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To generalize modern indications for bismuth drugs at treatment of gastroenterological diseases, and to estimate safety of their application basing on the literature data.Original positions. Preparations of bismuth (first of all – bismuthate tripotassium dicitrate) can be applied as main component of helicobacter eradication modes of the second (and in some cases – the first) line, as a drug for monotherapy for acute infectious diarrhea (in particular – travellers diarrheas), and also several chronic bowel diseases (postinfectious IBS, lymphocytic and collagenous colitis). Short (4–8 wks) courses of bismuth treatment are well tolerated by patients, are safe and do not cause serious side effects.Conclusion. Carried out analysis testifies that agents of bismuth still take the important place in the treatment of gastroenterological diseases.